Personality profile of combat sports champions against neo-gladiators - Piepiora, P.; Witkowski, K. (Archives of Budo, 2020)
Background and Study Aim: The problem, which has long been the area of interest of sport psychologists, trainers and athletes, concerns the determination of the personality factors of the master in sport. This specific task would have to be to determine the personality traits of athletes that are necessary for their success in sport. It is accepted to assume that sport shapes the personality of athletes (players), and this is characteristic of specific sports disciplines. A new phenomenon is the acceptance by certain social circles of neo-gladiatorialism (an example of mix martial arts - MMA) and camouflaging this pathology as part of combat sports. The aim of the research is the personality profiles of combat sports champions and neo gladiators based on the methodological criteria of the Big Five model.